2022
DOI: 10.1186/s12885-021-09145-0
|View full text |Cite
|
Sign up to set email alerts
|

Late effects of high-dose methotrexate treatment in childhood cancer survivors—a systematic review

Abstract: Background High-dose methotrexate (HD-MTX) is used in the treatment of different childhood cancers, including leukemia, the most common cancer type and is commonly defined as an intravenous dose of at least 1 g/m2 body surface area per application. A systematic review on late effects on different organs due to HD-MTX is lacking. Method We conducted a systematic literature search in PubMed, including studies published in English or German between 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…High‐dose methotrexate (HD‐MTX) therapy impairs neurocognitive outcomes in patients with childhood cancer 1 . There have been multiple reports of cognitive dysfunction after chemotherapy in patients with acute lymphoblastic leukemia (ALL), including those who had not received cranial radiation therapy 2 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…High‐dose methotrexate (HD‐MTX) therapy impairs neurocognitive outcomes in patients with childhood cancer 1 . There have been multiple reports of cognitive dysfunction after chemotherapy in patients with acute lymphoblastic leukemia (ALL), including those who had not received cranial radiation therapy 2 .…”
Section: Figurementioning
confidence: 99%
“…High-dose methotrexate (HD-MTX) therapy impairs neurocognitive outcomes in patients with childhood cancer. 1 There have been multiple reports of cognitive dysfunction after chemotherapy in patients with acute lymphoblastic leukemia (ALL), including those who had not received cranial radiation therapy. 2 As the cumulative dose of MTX used for standard osteosarcoma treatment is higher than that used for the treatment of ALL, we prospectively evaluated cognitive function in pediatric patients diagnosed with osteosarcoma.…”
mentioning
confidence: 99%
“…Methotrexate and cytosine arabinoside (araC) are toxic to the central nervous system (CNS), with both acute toxicity and worsened subsequent neurocognitive performance having been well-documented, correlating with leuko-encephalopathic changes on magnetic resonance imaging (MRI) scanning [ 50 ]. Children treated with high-dose intravenous methotrexate show significantly worse performance in neurocognitive testing, especially on the subscales of processing speed, memory, and sustained attention [ 51 ]. Children receiving intrathecal methotrexate performed worse in testing of intelligence, executive function, attention, visual perception, and short-term memory in comparison with those who did not have intrathecal treatment [ 52 ].…”
Section: Causes Of Neurocognitive Damagementioning
confidence: 99%
“…Subacute MTX neurotoxicity typically occurs 2–14 days after prolonged low-dose oral, intrathecal, or high-dose MTX and manifests with transient stroke-like symptoms, encephalopathy, seizures, and/or aphasia. Late effects may include seizures, memory loss, and problems related to academic achievement and attention ( Bhojwani et al, 2014 ; Daetwyler et al, 2022 ). Although the late effects of MTX treatment have been recognized for years, the mechanism of its pediatric neurotoxicity is not well understood ( Daetwyler et al, 2022 ).…”
mentioning
confidence: 99%
“…Late effects may include seizures, memory loss, and problems related to academic achievement and attention ( Bhojwani et al, 2014 ; Daetwyler et al, 2022 ). Although the late effects of MTX treatment have been recognized for years, the mechanism of its pediatric neurotoxicity is not well understood ( Daetwyler et al, 2022 ). Animal model studies using mice have revealed a decrease in myelin sheath thickness in the white matter of MTX-treated mice and depletion of oligodendrocyte lineage cells compared to controls ( Gibson et al, 2019 ; Mateos et al, 2022 ; Umugire et al, 2022 ).…”
mentioning
confidence: 99%